EVALUATION OF THE EFFECTIVENESS OF LABOR INDUCTION IN OBESE WOMEN - Abdurazakova, M.D.; Abdishukurova, M.U. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Artificial induction of labor is one of the most important methods used in practice, especially among pregnant women with a high body mass index. This article studies the effectiveness of labor induction in obese women and the risk of complications during labor. During the study, pregnant women with a body mass index of more than 30 kg/m2 and women of normal weight were divided into groups, and indications for labor induction, the duration of induction, the course of labor, the need for cesarean section, obstetric and perinatal complications were studied. The results of the analysis showed that obesity can negatively affect the outcome of induction, leading to a delay in the development and course of labor, and an increased need for cesarean section. Also, in certain situations, a correctly selected induction method can ensure a safe delivery for mother and child. This study substantiates the importance of an individual approach in working with women with obesity.